2015
DOI: 10.1080/03057240.2015.1043874
|View full text |Cite
|
Sign up to set email alerts
|

Humiliated self, bad self or bad behavior? The relations between moral emotional appraisals and moral motivation

Abstract: It has often been found in the literature that guilt motivates reparative behavior and that shame elicits aggressive reactions. However, recent research suggests that it is not the experience of shame, but rather the experience of humiliation that triggers aggressive reactions. The present study focuses on the role of shame, guilt and humiliation appraisals in predicting the motivation to repair and be aggressive in four different countries, namely Argentina, Belgium, Finland and Portugal. Using multi-group st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 40 publications
(57 reference statements)
0
7
0
Order By: Relevance
“…When the TOSCA is examined with factor analysis, the highest loading items on the guilt scale refer to reparative behavior, and therefore is has been questioned to what extent this scale measures emotion instead of behavioral tendencies. On the other hand, prosocial motivation is empirically so strongly associated with other elements of guilt that this distinction does not really seem to exist ( Silfver-Kuhalampi et al, 2013 , 2015 ). In terms of shame, the TOSCA shame scale emphasizes aspects of negative self-esteem, feeling worthless and bad as a person.…”
Section: Introductionmentioning
confidence: 99%
“…When the TOSCA is examined with factor analysis, the highest loading items on the guilt scale refer to reparative behavior, and therefore is has been questioned to what extent this scale measures emotion instead of behavioral tendencies. On the other hand, prosocial motivation is empirically so strongly associated with other elements of guilt that this distinction does not really seem to exist ( Silfver-Kuhalampi et al, 2013 , 2015 ). In terms of shame, the TOSCA shame scale emphasizes aspects of negative self-esteem, feeling worthless and bad as a person.…”
Section: Introductionmentioning
confidence: 99%
“…However, we also expect that moral shame would discourage topic avoidance, because self-perceived morality can only be restored by acting more moral in the present, and avoiding the topic is not moral behaviour. In previous research, moral shame has indeed been shown to be associated with a greater willingness to compensate and apologize, as well as a lower desire for self-defensive behaviour (Silfver-Kuhalampi, Figueiredo, Sortheix, & Fontaine, 2015;Allpress et al, 2014;Gausel et al, 2012). We therefore expect that moral shame will be associated with greater support for offering apologies and compensation and a lower desire to avoid the topic.…”
Section: The Role Of Moral Emotionsmentioning
confidence: 81%
“…These responses can be more internally or externally directed; Freud (1960) observed that repression originates in shame internalisation. Likewise, “feeling worthless and flawed is so painful that it is easier to shift the blame outward and feel angry towards others, sometimes leading to aggression” (Silfver-Kuhalampi, Figueiredo, Sortheix, & Fontaine, 2015, p. 217), particularly in response to perceived humiliation. Similarly, feeling shame can also lead to shaming of the other in an attempt to rid ourselves of the painful emotion.…”
Section: What Is Shame? a Partial (And Shamefully Inadequate) Reviewmentioning
confidence: 99%
“…While part of the universal human condition, shame and guilt are culturally specific and exhibited differently across time, place, and society (see, e.g., Harre, 1986). For example, Japanese children have been shown to more readily experience shame over guilt compared to American school children (Bear, Uribe-Zarain, Manning, & Shiomi, 2009; Silfver-Kuhalampi et al, 2015); additionally, guilt and shame serve distinct functions, and manifest differently, depending on the cultural context (Bear et al, 2009).…”
Section: What Is Shame? a Partial (And Shamefully Inadequate) Reviewmentioning
confidence: 99%